The Flipped Classroom as a Strategy for Pedagogical Innovation in Higher Education. - Vélez-Ulloa, Joe Ronald; Ramírez-Cabrera, Homero Abel; Morán-Quijije, Eduardo Erasmo; CEDEÑO SALAZAR, PEDRO ANTONIO (Revista Minerva, 2025)
This systematic review article aims to analyze the benefits and challenges of implementing the flipped classroom in higher education, based on a review of academic studies published in various regionally and internationally indexed journals. A mixed-methods approach was applied, combining quantitative and qualitative perspectives, and the PRISMA protocol was used to select and evaluate the 20 scientific articles included in the review, which cover different disciplines and multiple countries. The findings indicate that the flipped classroom fosters student motivation, classroom participation, autonomy, and improved academic performance, while also enhancing soft skills and collaborative problem-solving. However, challenges were also identified, such as the lack of technological infrastructure, cultural resistance to change, and the need for specialized teacher training to ensure effective implementation. The study concludes that, although this pedagogical strategy holds great potential to transform higher education, its success largely depends on institutional support, curricular planning, and faculty commitment; therefore, higher education institutions must provide adequate support to maximize the benefits identified in classroom practice.